Recent Acquisitions, Pierides Museum - Antoniou, Klitsa (My University, 2026)
Recent Acquisitions, Pierides Museum, Marfin Laiki Cultural Center, Selection of Monographs Text: Andrea Costantinou, Cyprus 2008